Experimental investigation into the effects of meteoritic impacts on the spectral properties of phyllosilicates on Mars. Issue 1 (30th January 2013) - Gavin, P.; Chevrier, V.; Ninagawa, K.; Gucsik, A.; Hasegawa, S.
Abstract : Phyllosilicates have been identified in some of the most highly cratered Noachian terrains on Mars. To study the effects of such impacts on the properties of phyllosilicates, we experimentally shocked six phyllosilicate minerals relevant to the Martian surface: montmorillonite, nontronite, kaolinite, prehnite, chlorite, and serpentine. The shock‐treated samples were analyzed with X‐ray diffraction (XRD), near‐ and mid‐infrared (NIR and MIR) spectroscopy, Raman spectroscopy, cathodoluminescence (CL), and the shock pressures and temperatures in some were modeled using Autodyn modeling software. XRD data show that the structure of each mineral, except prehnite, underwent partial structural deformation or amorphization. We also found that while the NIR spectra of shocked samples were very similar to that of the original sample, the MIR spectra changed significantly. This may explain some of the discrepancies between CRISM/OMEGA data (NIR) and TES/THEMIS (MIR) observations of phyllosilicates on Mars. Quartz was identified as a secondary phase in the XRD of shocked chlorite. Key Points: Shock deformation of phyllosilicates occurs at relatively low pressures Mid‐infrared spectra of phyllosilicates are strongly altered by shock treatment Shock alteration may cause differences between IR observations of Martian clays